Six species of thrips (Insecta: Thysanoptera) newly recorded from India with the description of Bamboosiella semiflava Okajima. (2nd January 2022) - Singha, Devkant; Chakraborty, Rajasree; Kumar, Vikas; Tyagi, Kaomud
ABSTRACT: Six species of order Thysanoptera, Bamboosiella semiflava Okajima, Praepodothrips causiapeltus Reyes, Podothrips ferrugineus Okajima, under family Phaleothripidae and Copidothrips octarticulatus (Schmutz), Neohydatothrips masrensis (Priesner), Scirtothrips hitam Ng, Mound & Azidah under family Thripidae are recorded new to India. The diagnostic characters of five species and first description of the male of Bamboosiella semiflava are discussed. The partial sequence data of mitochondrial cytochrome c oxidase (mtCOI) for all newly recorded species is generated and submitted to the Barcode of Life Data System (BOLD) except N. masrensis (Priesner) and C. octarticulatus (Schmutz).